Benefits and Costs of Public Schooling in Ghana - Raju, Dhushyanth (World Bank, Washington, DC, 2022)
This paper examines the monetary benefits and costs of the quantity of public schooling (that is, years of schooling completed) in Ghana. The paper also examines the monetary benefits and costs of some aspects of the quality of public schooling, measured by the gains in achievement produced by selected interventions in public schools. The analysis uses estimates of (i) labor-earnings returns to schooling and private spending on public schooling, based on the latest national household sample survey data; (ii) government spending on public schooling, based on administrative information; (iii) impacts on test scores, and costs, of education interventions in public schools, drawn from experimental studies; and (iv) conversions of impacts on test scores produced by education interventions to (future) labor earnings, all for Ghana. The results are a set of benefit-cost ratios in the style of the Copenhagen Consensus.